Japan rearmed : the politics of military power - Smith, Sheila A., 1959- (Harvard University Press, 2019)
Article Nine of Japan's postwar constitution, drafted in 1946 under U.S. Occupation, claims that the Japanese people "forever renounce the use of force as a means of settling international disputes." During the Cold War, the alliance with the United States allowed Japan to develop a largely defensive military, the Self-Defense Forces. Yet in the decades since, Japan has considered new ways to use its military. Demands from Washington for greater Japanese military participation in coalition forces and a gradual embrace in Japan of contributing to UN peacekeeping led to overseas deployments. Entering the 21st century, North Korea's nuclear and missile proliferation and China's growing maritime assertiveness have challenged Japanese strategists to confront their hesitancy over the use of force. This book examines this ambivalence over the military as an instrument of power and argues that the accelerating changes in Japan's relationship with the United States and with its neighbors are forcing Tokyo's political leaders to confront the idea that they may need to order their military to do what all militaries are expected to do: prepare for war.--